The roles of ions on bone regeneration. Issue 4 (April 2018) - O'Neill, Edward; Awale, Guleid; Daneshmandi, Leila; Umerah, Obum; Lo, Kevin W.-H.
Highlights: Alternative bone regenerative therapeutics are needed. Ions have been proposed to regenerate skeletal tissue. Drug delivery systems have been studied to deliver ions for bone regeneration. Abstract : Bone scientists are actively investigating a range of methods to promote skeletal tissue regeneration. A review of recent literature has revealed that several ions are uniquely capable of inducing stem cell differentiation down desired lineages. There exists enormous promise for these ions to be used in bone regenerative medicine. Given that these ions can be released from biodegradable polymeric materials, their long-term delivery can be achieved through a variety of controlled-release strategies compared with the relatively few options available for expensive and fragile polypeptide-based growth factors. In this review, we highlight the developments in using ions in conjunction with biomaterials for bone regeneration.